2013
DOI: 10.1242/jeb.081984
|View full text |Cite
|
Sign up to set email alerts
|

The physiological response of the marine platyhelminthMacrostomum lignanoto different environmental oxygen concentrations

Abstract: SUMMARYThe respiration rate of meiofauna is difficult to measure, and the response to variations in the environmental oxygen concentration has so far been mainly addressed through behavioral investigation. We investigated the effect of different oxygen concentrations on the physiology of the marine platyhelminth Macrostomum lignano. Respiration was measured using batches of 20 animals in a glass microtiter plate equipped with optical oxygen sensor spots. At higher oxygen saturations (>12kPa), the animals show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 58 publications
2
31
0
2
Order By: Relevance
“…As the experimental set-up only requires organisms that are viable in liquid culture and have a size that fits the transient microchamber (XF96: 3 μl, XF24: 7 μl), mitochondrial respiration can also be estimated in species other than C. elegans. Therefore, Seahorse XF respirometers might open new avenues for other well-established or upcoming species that may be used in metabolic or aging studies, such as the flatworm Macrostomum lignano 56, Danio Rerio embryos5758 and even Nothobranchius furzeri embryos59. While XF respirometers are, to our knowledge, not used in Macrostomum lignano or Nothobranchius furzeri research yet, it has been shown that respiratory kinetics in embryos from Danio Rerio can be investigated with XF respirometers58.…”
Section: Alternative Applicationsmentioning
confidence: 99%
“…As the experimental set-up only requires organisms that are viable in liquid culture and have a size that fits the transient microchamber (XF96: 3 μl, XF24: 7 μl), mitochondrial respiration can also be estimated in species other than C. elegans. Therefore, Seahorse XF respirometers might open new avenues for other well-established or upcoming species that may be used in metabolic or aging studies, such as the flatworm Macrostomum lignano 56, Danio Rerio embryos5758 and even Nothobranchius furzeri embryos59. While XF respirometers are, to our knowledge, not used in Macrostomum lignano or Nothobranchius furzeri research yet, it has been shown that respiratory kinetics in embryos from Danio Rerio can be investigated with XF respirometers58.…”
Section: Alternative Applicationsmentioning
confidence: 99%
“…The few works that had measured ROS levels using chemical probes indicate that indeed ROS formation still occurs during oxygen deprivation (even in animals under anoxia) (Milton et al, 2007;Rivera-Ingraham et al, 2013a;RiveraIngraham et al, 2013b), but, so far, there is no report of increased ROS in such situations. On the other hand, there are many pieces of indirect evidence that indicates that ROS levels should rise.…”
Section: 2 Limitations On the Pos Mechanistic Proposalmentioning
confidence: 99%
“…In contrast to mammalian cells, fewer studies have assessed ROS production in animals that are naturally exposed to low oxygen stress. A study using in vivo staining with the nonspecific ROS detector C-H 2 DFFDA, evidenced that the marine platyhelminthes Macrostomum lignano ROS formation follows the typical oxygenation-dependent pattern(Rivera-Ingraham et al, 2013a). However, superoxide formation (DHE staining) remained constant across oxygenation conditions (ranging from hyperoxia (40 kPa) to near-anoxia), and only reoxygenation caused a 2-OH-E + :DHE ratio increase.…”
mentioning
confidence: 99%
“…ASW was continuously aerated with humidified filtered air (0.2 lm) of different partial pressures of CO 2 in 5-l Duran borosilicate bottles equipped with glass frits. This manipulation method is the most appropriate to reproduce the expected situation influenced by atmospheric CO 2 concentrations (Riebesell et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The CO 2 partial pressures were selected according to the literature (Riebesell et al 2010;IPCC-Report 2007) to represent atmospheric conditions during the last glacial maximum and the present conditions (measured pCO 2 between 180-425 latm), projected acidification scenarios by the end of the century and increased/extreme values (acidified conditions with measured pCO 2 *550-800, *1,300 and *2,000 latm).…”
Section: Methodsmentioning
confidence: 99%